Students Motivation and Learning Output at Permodalan Koperasi Course of Program Studi Pendidikan Ekonomi through Application of Gagne’s Cognitive Model - Ekawarna, Ekawarna; Irwan, Irwan (UI Scholars Hub, 2010)
The purpose of this research are to (1) increasing result of student learning in Program Studi Pendidikan Ekonomi Jurusan PIPS FKIP Universitas Jambi at Permodalan Koperasi course in order to obtain minimum average score